2011
DOI: 10.12671/jkfs.2011.24.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment with Gamma 3 Nail in Femur Intertrochanteric Fracture

Abstract: Purpose: To evaluate clinical and radiological results of surgical treatment of femur intertrochantenric fracture using Gamma 3 nail. Materials and Methods: With clinical study, 22 patients who were treated surgically by Gamma 3 nail were retrospectively evaluated. By postoperative radiograph and last follow up radiograph we measured Tip-apex distance, Cleveland index, Neck-shaft angle change Lag screw slippage and Union time. And By medical record review, the clinical results were evaluated with the operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Advantages of intramedullary nailing include biomechanical superiority and structural stability enabling immediate postoperative rehabilitation regardless of the fracture type 4 5 6) . Previous studies have reported favorable clinical and radiographic outcomes for proximal femoral nail antirotation (PFNA; Synthes, Oberdorf, Switzerland) with a helical blade and a single-screw-system (Gamma 3 Locking Nail System; Stryker, Schoenkirchen, Germany) 8 9 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of intramedullary nailing include biomechanical superiority and structural stability enabling immediate postoperative rehabilitation regardless of the fracture type 4 5 6) . Previous studies have reported favorable clinical and radiographic outcomes for proximal femoral nail antirotation (PFNA; Synthes, Oberdorf, Switzerland) with a helical blade and a single-screw-system (Gamma 3 Locking Nail System; Stryker, Schoenkirchen, Germany) 8 9 10) .…”
Section: Introductionmentioning
confidence: 99%